Utilização do tanino condensado do sabiá (Mimosa caesalpinifolia) e da Acácia negra (Acacia mearnsii) sobre nematóides gastrintestinais em caprinos - PIRES FILHO, Pedro Celestino Serejo (2023)
The use of vegetables with a high concentration of condensed tannins has demonstrated great viability for the control of gastrointestinal parasites, since infection by nematodes has caused enormous economic losses and becomes one of the biggest health problems in the production of small ruminants. The objective of this research was to evaluate the use of condensed tannin from thrush (Mimosa caesalpinifolia) and black wattle (Acacia mearnsii) on gastrointestinal nematodes in goats. The bark powder of A. mearnsii was supplied by the company Seta Sun® and of M. caesalpinifolia it was obtained directly from the leaf of the plant. The leaves of M. caesalpiniifolia were collected, dried and ground. To obtain the acetonic extracts, 200 mg of powder from the respective vegetables were used in 10 mL of 70% acetone. Finally, the mixture was sonicated for 20 minutes. The extract was subjected to analysis of total phenols, total tannins and condensed tannins. For the in vivo study, 30 crossbred Anglonubian goats, aged approximately 12 months and mean body weight of 22.62 ± 1.33 kg, were used. Of these, 16 goats were pregnant. To separate the groups, the number of pregnancies, the mean weight and the mean EPG per group were considered. Thus forming three groups: the control group (GC) that received only the concentrate, the second group (GT1) that received feed with a ratio of tannins 50:50 and the third group (GT2) that received feed with a ratio of 70:30. The rations are isoproteic and isoenergetic. These were used as supplementation for the animal, being administered in a proportion equivalent to 3% of live weight. To evaluate the reduction of eggs per gram of feces, the of the groups were performed weekly. The quantification of condensed tannins from both plants showed 12.03% for M. caesalpiniifolia and 25.4% for A. mearnsii. It was observed that the inclusion of Mimosa caesalpiniifolia leaf powder and Acacia mearnsii bark powder in goat diets caused a reduction in the count of the number of EPG in the treated animals of the GT1 group, in relation to the control group CG and group GT2, however, this difference was not statistically significant (P > 0.05). It was found that the amount of tannins of 0.25 g.kg BW-1 caused adverse effects, such as reduced palatability of the feed, allowing adequate voluntary consumption of tannin supplementation. However, more research is needed on the use of plant tannins for ruminant production and health purposes.